Case Report: A Case Report and Literature Review of 3p Deletion Syndrome - Fu, Junxian; Wang, Ting; Fu, Zhuo; Li, Tianxia; Zhang, Xiaomeng; Zhao, Jingjing; Yang, Guanglu (Frontiers in Pediatrics, 2021)
Objective: The aim of the present study is to explore the clinical and genetic characteristics of 3p deletion syndrome to improve clinicians' understanding of the disease. Methods: The clinical manifestations, process of diagnosis and treatment, and genetic characteristics of an individual case of 3p deletion syndrome were analyzed. CNKI, Wanfang Data, and the Biomedical Literature Database (PubMed) were searched. The search time limit, using “3p deletion syndrome” and “BRPF1” as keywords, was from the creation of the database up to June 2020. Related data were reviewed. Results: The proband was a male child with general developmental and intellectual disabilities, special facial features and congenital heart disease. The child was the parents' first pregnancy and first born. Gene microarray analysis showed a 10.095 Mb deletion in the 3p26.3-p25.3 region, resulting in a heterozygous mutation of the BRPF1 gene; thus, the patient was diagnosed with 3p deletion syndrome. At the time of diagnosis, the child was 1 year of age and was responding to comprehensive rehabilitation training. A total of 29 well-documented cases were found in the literature, of which 19 cases had an onset within 1 year of birth, and mainly manifested with mental and motor development disabilities and abnormal facial features, with different gene deletions, depending on the size and location of the 3p deletion. Conclusion: The genetic test results of the child in this study indicated a heterozygous deletion of the BRPF1 gene on the short arm of chromosome 3, which was a unique feature of this study, since it was rarely mentioned in other reports of 3p deletion syndrome. The clinical phenotype of this syndrome is complex as it can include intellectual and motor development backwardness, low muscle tone, certain abnormal facial features (low hairline, bilateral ptosis, widely spaced eyes, a forward nose, left ear auricle deformity, a high-arched palate, a small jaw), and the deformation of systems such as the gastrointestinal tract and the urinary tract malformation or symptoms of epilepsy. As clinical manifestations can be relatively mild, the syndrome is easy to miss or misdiagnose. Clinical workers need to be aware of this disease when they find that children have special features, such as stunted growth, low muscle tone or ptosis, and it needs to be diagnosed through genetic testing. Most children are able to develop certain social skills after rehabilitation treatment.